Correlation between clinical, MRI and arthroscopic findings in various shoulder joint disorders - Gupta, Ayush; Agrawal, Atul; Kumar, Sanad; Raghuvanshi, Shailendra; Siddiqui, Faiz Akbar (International Journal of Research in Orthopaedics, 2025)
Background: Shoulder joint is the most freely moveable, but a relatively unstable joint in the body. The most commonly used currently prevalent diagnostic tools for shoulder joint disorders are clinical examination, Magnetic Resonant Imaging (MRI) and the gold standard arthroscopy. All have their inherent advantages and disadvantages and none is an all-inclusive tool. Furthermore, the current literature lacks studies comparing all the three diagnostic tools together or has just included one or two of the wide array of shoulder joint disorders. Therefore, this study was undertaken to identify correlation between all three diagnostic methods in arriving at a diagnosis in various shoulder disorders taking arthroscopy as a gold standard. Methods: The study was a prospective descriptive study carried out at a tertiary care hospital over period of 2 years. 33 symptomatic shoulder patients underwent standardized history, physical examination and MRI prior to diagnostic/therapeutic arthroscopy procedure. Shoulder arthroscopy considered as the gold standard, was used as a benchmark for comparing and confirming the results of clinical and radiological findings using the standard statistical data analysis. Results: Amongst clinical and radiological (MRI) findings; clinical examination was found to be superior to MRI in diagnosing adhesive capsulitis and bicipital tendinitis; MRI was found to be superior to clinical examination for diagnosing rotator cuff tears and Gleno-Humeral (GH) arthritis; both were equivocal in diagnosing Sub-Acromial Impingement Syndrome (SAIS), GH instability and Superior Labrum Anterior Posterior (SLAP) lesions. Conclusions: No modality in isolation is accurate and a combination of various available diagnostic tools gives the best precision in diagnosing shoulder joint disorders.